The role of mGluR5 during conditioned hyperactivity and sensitization in differentially reared rats - Gill, Margaret J. (Kansas State University, 2010)
Glutamate contributes to the neurological and behavioral changes that occur during differential rearing, and those that occur during conditioned hyperactivity and sensitization. Metabotropic glutamate receptor 5 (mGluR5) in particular contributes to the psychostimulant reward pathway, plasticity, and differential rearing. The present study examined the role of mGluR5 in conditioning and sensitization in differentially reared rats. Rats were reared in an enriched (EC), impoverished (IC), or social (SC) condition for 30 days, after which they received repeated amphetamine (0.3 mg/kg) or saline injections. Following training, rats received an injection of the mGluR5 antagonist MTEP or saline prior to undergoing conditioned hyperactivity and sensitization tests. Results showed that MTEP attenuated conditioned hyperactivity and sensitization in IC but not EC and SC rats, suggesting that glutamatergic changes occur during differential rearing that alter the effects of MTEP on amphetamine conditioning and sensitization. Additionally, results demonstrated that enrichment rearing has a protective effect against conditioned hyperactivity at low doses of amphetamine.
Keywords: Sprague Dawley; Amphetamine; Differential Rearing; mGluR5; Conditioned Hyperactivity; Sensitization; Psychology, Behavioral (0384); Psychology, Psychobiology (0349)